Cultivating cyber-phronesis: a new educational approach to tackle cyberbullying. (1st October 2016) - Harrison, Tom
Abstract: Cyberbullying is a pervasive and troubling moral concern for teachers, schools, parents and pupils. As children and young people in England are now more likely to be bullied online than face-to-face, this article explores if there is a need to rethink traditional educational approaches to dealing with the issue. The article starts with a critique of the current dominant approaches to tackling cyberbullying in schools, which draw predominantly on deontological and utilitarian moral philosophies. It then details what an Aristotelian character education approach to cyberbullying would consist of. At its heart is a requirement to enable children and young people to become digitally virtuous citizens, through the development of cyber-phronesis. The article concludes with a description of moral educational interventions that would increase the likelihood of children and young people making both 'good' and 'wise' choices when online.